Peningkatan Kemampuan Mengenal dan Mengingat Lambang Bilangan 1-10: Melalui Permainan Kartu Angka Pada Anak Usia Dini - Amelia Pramesti; Azizah Andestria; Adhelia Rainy; Eni Epriani; Risti Wika Julianti; Fidhia Wika Andani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The ability to recognize and memorize number symbols is one of the most critical cognitive developmental milestones for early childhood. However, numerous findings suggest that many children aged four to five years still struggle to independently identify and recall number symbols, particularly when instruction relies on passive and monotonous methods. This study aims to examine in depth how number card games can serve as an effective strategy for improving children's ability to recognize and remember number symbols from 1 to 10. A descriptive qualitative approach was employed by reviewing and synthesizing findings from relevant prior studies. Data sources consisted of national and international journal articles selected based on topic relevance, data currency, and source credibility. The findings consistently demonstrate that number card games improve children's numerical memory through dual coding mechanisms, multimodal stimulation, meaningful repetition, and social scaffolding within play groups. This study concludes that structured and varied number card game implementation is both developmentally appropriate and empirically effective for children aged 4–5 years.